Production of avian leukosis virus particles in mammalian cells can be mediated by the interaction of the human immunodeficiency virus protein Rev and the Rev-responsive element. - Nasioulas, G (1995)
In human immunodeficiency virus type 1-infected cells, the efficient expression of viral proteins from unspliced and singly spliced RNAs is dependent on two factors: the presence in the cell of the viral protein Rev and the presence in the viral RNA of the Rev-responsive element (RRE). We show here that the HIV-1 Rev/RRE system can increase the expression of avian leukosis virus (ALV) structural proteins in mammalian cells (D-17 canine osteosarcoma) and promote the release of mature ALV virions from these cells. In this system, the Rev/RRE interaction appears to facilitate the export of full-length unspliced ALV RNA from the nucleus to the cytoplasm, allowing increased production of the ALV structural proteins. Gag protein is produced in the cytoplasm of the ALV-transfected cells even in the absence of a Rev/RRE interaction. However, a functional Rev/RRE interaction increases the amount of Gag present intracellularly and, more strikingly, results in the release of mature ALV particles into the supernatant. RCAS virus containing an RRE is replication-competent in chicken embryo fibroblasts; however, we have been unable to determine whether the particles produced in D-17 cells are as infectious as the particles produced in chicken embryo fibroblasts.